Social Marketing Strategy for Social Care Programs for Victims of Human Trafficking Crimes - Almogbel, Ahmed Nasser; Elrashidy, Abdelwanis mohamed (Journal of Ecohumanism, 2024)
This study aimed to determine the social marketing strategy for social care programs for victims of human trafficking crimes by identifying the reality, mechanisms, challenges, and proposals for activating social marketing for social care programs for victims of human trafficking crimes. The research is descriptive research that aims to describe the social marketing strategy for social care programs for victims of human trafficking crimes. In line with the type of research, the researcher relied on the social survey method with a sample, which is one of the most appropriate methods for descriptive research. The research community was represented by officials in the department of combating human trafficking crimes at the Ministry of Human Resources and Social Development and in shelter centers in the kingdom’s regions. The research sample was determined by a simple random sample of officials in the Department of Combating Human Trafficking Crimes at the Ministry of Human Resources and Social Development and shelter centers in the kingdom’s regions, consisting of 121 individuals. The research results confirmed that The challenges of social marketing for social care programs for victims of human trafficking crimes were represented in: interest in superficial advertising aspects of social marketing, lack of marketing skills among those in charge of social marketing programs, lack of good planning for social marketing programs, and poor training of workers in the field of social marketing. The proposals to activate social marketing for social care programs for victims of human trafficking crimes represented: interest in conducting social surveys to determine the needs of victims, building a specialized department in social marketing for social care programs for victims of human trafficking crimes, interest in realistic advertising aspects of social marketing, and measuring victims’ satisfaction with the programs scientifically provided to them.